Inspecting the Impact of WFH Policy on Indonesian Workers to Help Improve Human Resources Quality During Pandemic - Nusrhotun Aristia Zulfa; Mona Zulfa Aszar; Markus Apriono (UPT Penerbitan Universitas Jember, 2021)
This article pursues to provide an overview of WFH as a virtual communication medium, that can be used in work affairs in the new normal era. As well as the WFH policy analysis of the Indonesian worker's performance quality during the Covid-19 pandemic. That analysis is conduct so that the next time the quality of human resources and worker productivity can be improved even though it is still through WFH (working from home). And it is also hoped that this WFH policy can become a means of communication infrastructure in the future life in the new normal era. The method we use is a qualitative approach method. Qualitative research is research that is descriptive and tends to use analysis. Process and meaning are highlighted in qualitative research. This article yields the result that WFH has pros and cons, but it has a high chance to be continued with the awareness of employees to build a good atmosphere at home such as a special environment for work. Meanwhile, a management and leadership system from superiors is also needed to protect subordinates, and a two-way effort is needed either from employees or managers. Keywords: Covid-19, New Normal, WFH, WFO, Worker Productivity